Measuring Total Factor Productivity Growth in Agriculture in Libya (1980-2020): Malmquist Index: Total Factor Productivity Growth in Agriculture - alabasi, hanan (Surman Journal of Science and Technology, 2022)
The study addressed the measurement of the growth of total productivity of agricultural factors of production in Libya during 1980-2020. It was based on a basic hypothesis that there is a weakness in the growth of total productivity of production factors. The low contribution of agriculture to the gross domestic product makes it imperative to study the reasons behind this. Measuring the growth of total productivity of production factors is one of the factors that affect the rates of total agricultural production, including knowing the efficiency in the use of resources and thus avoiding the waste of resources. This paper used the Malmquist index to measure the growth rate of total productivity of agricultural factors in Libya from 1980 to 2020. The data were collected from the World Food Organization and the World Bank. The results showed that the average growth of total productivity of production factors during the study period was only 0.6%, and this rate reflects the slow growth of productivity and that the growth rate of total productivity of production factors accelerated during the last two decades and was less than one in the eighties and nineties. While there was growth in agricultural productivity from 2001 to 2020. In general, during the general average of technical efficiency for four decades, it was about 64%, meaning that the same average production could be obtained by reducing 36% of the quantities of production factors. And 11% of the land element, 24% of the labor element, 2% of the irrigated land element, 6% of the number of tractors, 7% of fertilizers, and 3% of the number of animals could have been dispensed with to produce the total amount. Hence, the study recommends the need to make efforts to develop and improve the performance of the agricultural sector through the efficient use of production inputs